Submarine Slope Stability of a Fjord Delta: Bella Coola, British Columbia - Kostaschuk, Ray; McCann, S. (Géographie physique et Quaternaire, 1989)
ABSTRACTRecent evidence indicates that the submarine slopes of the Bella Coola Delta, a fjord delta in British Columbia, are subject to mass movements. Mass movements originate in the source areas of chutes (gullies) and transfer coarse sediment downslope. Stability analyses indicate that earthquakes, depositional loading and wave loading are capable of causing slope failures in chute source areas. Gas generation and tidal drawdown appear to reduce sediment strength by increasing pore water pressures, increasing the potential for failures initiated by other mechanisms. Failure related to slope over-steepening at distributary mouths would require much steeper slopes than those encountered. The most unstable areas are those at distributary mouths where most of the mechanisms of failure generation could occur simultaneously. With the exception of earthquakes, the failure mechanisms examined would result in high frequency, low magnitude slides that are most likely to occur in spring and summer. Earthquakes would cause high magnitude, low frequency failures.